The cost-effectiveness of small-quantity lipid-based nutrient supplements for prevention of child death and malnutrition and promotion of healthy development: modelling results for Uganda - Katherine P Adams; Stephen A Vosti; Charles D Arnold; Reina Engle-Stone; Elizabeth L Prado; Christine P Stewart; K Ryan Wessells; Kathryn G Dewey (Cambridge University Press, 2023)
Abstract Objective: Recent meta-analyses demonstrate that small-quantity lipid-based nutrient supplements (SQ-LNS) for young children significantly reduce child mortality, stunting, wasting, anaemia and adverse developmental outcomes. Cost considerations should inform policy decisions. We developed a modelling framework to estimate the cost and cost-effectiveness of SQ-LNS and applied the framework in the context of rural Uganda. Design: We adapted costs from a costing study of micronutrient powder (MNP) in Uganda, and based effectiveness estimates on recent meta-analyses and Uganda-specific estimates of baseline mortality and the prevalence of stunting, wasting, anaemia and developmental disability. Setting: Rural Uganda. Participants: Not applicable. Results: Providing SQ-LNS daily to all children in rural Uganda (> 1 million) for 12 months (from 6 to 18 months of age) via the existing Village Health Team system would cost ∼$52 per child (2020 US dollars) or ∼$58·7 million annually. SQ-LNS could avert an average of > 242 000 disability-adjusted life years (DALYs) annually as a result of preventing 3689 deaths, > 160 000 cases of moderate or severe anaemia and ∼6000 cases of developmental disability. The estimated cost per DALY averted is $242. Conclusions: In this context, SQ-LNS may be more cost-effective than other options such as MNP or the provision of complementary food, although the total cost for a programme including all age-eligible children would be high. Strategies to reduce costs, such as targeting to the most vulnerable populations and the elimination of taxes on SQ-LNS, may enhance financial feasibility.